The Importance of Education in The Tarikat of Naqshbandiya - Nilufar Tuychieva (Indonesian Journal Publisher, 2025)
This article describes the Naqshbandi tarikat widespread in Central Asia and the stages of maturity in it. the author talks about the levels of spiritual development of the Naqshbandis and their founders. Naqshbandiya shows the essence of the call for social activity and the encouragement of honest work.It also analyzes how important sect morals are in modern youth culture